CARDIOVASCULAR EFFECTS OF TWO AMIDES (PIPERINE AND PIPERDARDINE)ISOLATED FROM PIPER TUBERCULATUM JACQ. - Araújo-Júnior, João X. de; Araújo-Júnior, João X. de; Ribeiro, Êurica Adélia N.; Silva, Sâmia Andrícia S. da; Costa, Cintia Danieli F. da; Suzana Alexandre-Moreira, Magna; Santos, Bárbara V. O. (Emirates Journal of Food and Agriculture, 2011)
Cardiovascular activity of the fraction from the plant Piper tuberculatum, containing two amides, piperine and piperdardine (PTPP) was evaluated in this work. Intravenous injection of PTPP (1.5; 2.5 and 5.0 mg/kg, i.v.) in normotensive rats reduced the diastolic blood pressure (DBP) and heart hate (HR) in a dose dependent manner. This effect was affected in rats treated with methysergide (5 mg/Kg, i.v), an inespecific serotonergic antagonist. In anesthetized and ventilated animals, PTPP lowered the DBP and the HR in a significative manner. However these effects were completely abolished after bilateral cervical vagotomy. The PTPP relaxed phenylephrine or KCl 80 mM pre-contracted rat aortic artery rings both with intact or denuded endothelium. This response was independent of the presence of a functional vascular endothelium. These results taken together, suggest that the hypotension and bradicardia observed after PTPP is probably due to direct cardiac activation and as a result of a direct spasmolytic effect.